The influence of price, convenience of services, and implementation of health protocols on purchase decision of Garuda tickets - Tiwuk Ekasari (Indonesia Research and Study Center, 2023)
Purchasing decision is a process that starts from before the decision is taken until after the purchase decision has been made. The decision to purchase air transportation services, especially the decision to purchase Garuda tickets, is influenced by price factors, service convenience and the implementation of health protocol procedures. The purpose of this study was to determine the effect of price, convenience of service, and implementation of health protocols on purchasing decisions for Garuda tickets. The sample for this study was taken from the population of Garuda airline service users with a sample size of 100 respondents. The sampling technique is non-probability sampling with purposive sampling method. Methods of data collection using questionnaires and literature study. The analysis technique of this research is descriptive quantitative with operational definition of variables, instrument test with validity test, reliability test. The results showed that price (X1), convenience of service (X2) and health protocol procedures(X3) had a positive effect on the decision to purchase (Y) Garuda tickets. The f test shows that price, service convenience and health protocol procedures together have a significant effect on the decision to purchase Garuda tickets